1991
DOI: 10.1002/gj.3350260403
|View full text |Cite
|
Sign up to set email alerts
|

Genesis of lithium pegmatites from the leinster granite margin, southeast ireland: Geochemical constraints

Abstract: Extensive and economically-important lithium pegmatites have been described from the eastern flank of the large S-type peraluminous Leinster Granite batholith in southeast Ireland. This flank area is also the locus of a major dip-slip ductile shear zone which was active during emplacement of the Tullow Lowlands pluton of the batholith. All the known bedrock occurrences of lithium pegmatite are contained within this marginal deformation zone.Most previous studies have suggested derivation of the lithium pegmati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…The Leinster pegmatite belt has been the target of exploration drilling and academic research since the 1970s (e.g. Steiger and von Knorring, 1974;Luecke, 1981;O'Connor et al, 1991). Barros and Menuge (2016) provide a lithological description of the pegmatites and their host rocks at Aclare and Moylisha.…”
Section: Geologic Setting Previous Studies and Sample Materialsmentioning
confidence: 99%
“…The Leinster pegmatite belt has been the target of exploration drilling and academic research since the 1970s (e.g. Steiger and von Knorring, 1974;Luecke, 1981;O'Connor et al, 1991). Barros and Menuge (2016) provide a lithological description of the pegmatites and their host rocks at Aclare and Moylisha.…”
Section: Geologic Setting Previous Studies and Sample Materialsmentioning
confidence: 99%
“…the Li-rich and peraluminous Leinster Granite and pegmatites of SE Ireland with an initial 87 Sr/ 86 Sr of 0-705; O'Connor et al 1991). Multiple source rocks for cogenetic magmas of peraluminous granite-pegmatite systems (e.g.…”
Section: Isotope Systematicsmentioning
confidence: 99%
“…The Leinster Granite was emplaced during shearing (McArdle & Kennedy, 1985). Foliated Li pegmatites within this deformation zone have been dated at 396 + 7 Ma (O'Connor, Gallagher & Kennan, 1991). Unlike the Leinster Granite and minor intrusions within the East Carlow Deformation Zone, however, the Croghan Kinshelagh granite is not strongly foliated.…”
Section: C Structure and Metamorphismmentioning
confidence: 99%
“…In addition, recent Rb-Sr dating of the passively emplaced minor granitic and tonalitic sheets (e.g. Aughrim, Coolboy, Macreddin) shows them to be contemporaneous with the diorite suite (combined age 410+13 Ma) and perhaps to predate slightly the main batholith (O'Connor, Gallagher & Kennan, 1991). Brindley & Connor (1972) and Brindley & Gupta (1973) suggested that the Croghan Kinshelagh granite belonged to this suite of minor granitoids.…”
Section: Introductionmentioning
confidence: 99%